Enhancing tree performance through species mixing: Review of a quarter-century of TreeDivNet experiments reveals research gaps and practical insights - Leen Depauw; Emiel De Lombaerde; Els Dhiedt; Haben Blondeel; Luis Abdala-Roberts; Harald Auge; Nadia Barsoum; Jürgen Bauhus; Chengjin Chu; Abebe Damtew; Nico Eisenhauer; Marina V. Fagundes; et al. (My University, 2024)
Purpose of Review International ambitions for massive afforestation and restoration are high. To make these investments sustainable and resilient under future climate change, science is calling for a shift from planting monocultures to mixed forests. But what is the scientific basis for promoting diverse plantations, and what is the feasibility of their establishment and management? As the largest global network of tree diversity experiments, TreeDivNet is uniquely positioned to answer these pressing questions. Building on 428 peer-reviewed TreeDivNet studies, combined with the results of a questionnaire completed by managers of 32 TreeDivNet sites, we aimed to answer the following questions: (i) How and where have TreeDivNet experiments enabled the relationship between tree diversity and tree performance (including productivity, survival, and pathogen damage) to be studied, and what has been learned? (ii) What are the remaining key knowledge gaps in our understanding of the relationship between tree diversity and tree performance? and (iii) What practical insights can be gained from the TreeDivNet experiments for operational, real-world forest plantations? Recent Findings We developed a conceptual framework that identifies the variety of pathways through which target tree performance is related to local neighbourhood diversity and mapped the research efforts for each of those pathways. Experimental research on forest mixtures has focused primarily on direct tree diversity effects on productivity, with generally positive effects of species and functional diversity on productivity. Fewer studies focused on indirect effects mediated via biotic growing conditions (e.g. soil microbes and herbivores) and resource availability and uptake. Most studies examining light uptake found positive effects of species diversity. For pests and diseases, the evidence points mostly towards lower levels of infection for target trees when growing in mixed plantations. Tree diversity effects on the abiotic growing conditions (e.g. microclimate, soil properties) and resource-use efficiency have been less well studied to date. The majority of tree diversity experiments are situated in temperate forests, while (sub)tropical forests, and boreal forests in particular, remain underrepresented. Summary TreeDivNet provides evidence in favour of mixing tree species to increase tree productivity while identifying a variety of different processes that drive these diversity effects. The design, scale, age, and management of TreeDivNet experiments reflect their focus on fundamental research questions pertaining to tree diversity-ecosystem function relationships and this scientific focus complicates translation of findings into direct practical management guidelines. Future research could focus on (i) filling the knowledge gaps related to underlying processes of tree diversity effects to better design plantation schemes, (ii) identifying optimal species mixtures, and (iii) developing practical approaches to make experimental mixed plantings more management oriented.
Keywords: Mixed forest plantations · Tree diversity · TreeDivNet · Tree performance · Tree species mixing · Productivity · Afforestation